Correction to: Improving infant sleep safety via electronic health record communication: a randomized controlled trial - Ethan A. Canty; Benjamin N. Fogel; Erich K. Batra; Eric W. Schaefer; Jessica S. Beiler; Ian M. Paul (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.